2019
DOI: 10.1080/21691401.2019.1687505
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of phenformin on zebrafish embryonic neurodevelopmental toxicity induced by X-ray radiation

Abstract: Radiotherapy (RT) is a common treatment for head and neck cancers, but central nervous system function can be impaired by clinical radiation doses. This experimental study evaluated the protective efficacy of the anti-hyperglycaemic/anti-neoplastic agent phenformin against radiation-induced developmental toxicity in zebrafish embryos. Zebrafish embryos pre-treated with 25 lM phenformin 1 h before x-ray irradiation were compared to irradiation-only embryos for mortality, hatching rate, morphology, spontaneous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The difference between UV-234 and UV-328 may be due to the variations in their chemical structures. Previous studies have also suggested that different BUVs elicit unique responses in zebrafish or cells. , Moreover, the downregulation of p53 may lead to increased hatching and heart rates in zebrafish by inhibiting apoptosis . However, further investigations are necessary to fully elucidate the sequence of these cascading effects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between UV-234 and UV-328 may be due to the variations in their chemical structures. Previous studies have also suggested that different BUVs elicit unique responses in zebrafish or cells. , Moreover, the downregulation of p53 may lead to increased hatching and heart rates in zebrafish by inhibiting apoptosis . However, further investigations are necessary to fully elucidate the sequence of these cascading effects.…”
Section: Resultsmentioning
confidence: 99%
“…32,51 Moreover, the downregulation of p53 may lead to increased hatching and heart rates in zebrafish by inhibiting apoptosis. 52 However, further investigations are necessary to fully elucidate the sequence of these cascading effects.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In addition, ACh synthesis and degradation has to be in balance because sudden inhibition of AChE leads to paralysis and death. 38 Previous studies have established the presence of a feedback between AChE activity and ACHE transcription 39 41 as well as other feedback mechanisms involving changes in the BCHE expression and activity of BChE 42 44 and acetycholine receptors 40 , 45 acting as modulators of cholinergic signaling. 46 However, to our knowledge, there is no study in the literature testing the association between the enzyme activity and transcription levels of cholinesterases in response to the PTZ exposure in cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…Zebrafish embryos have been used as a unique vertebrate model to quickly screen therapeutic agents 46,47 . Zebrafish embryos are small, optically transparent and easily available, and have short embryonal development, which are conducive to quick and direct observation of radiation-induced damage to animals (death, deformation, abnormal organs and damaged DNA); thus, zebrafish embryos have also been used to study radiation-induced mutation and evaluate radioprotective agents including amifostine [48][49][50][51][52][53] . Here we used zebrafish embryos as the model to study the in vivo protection by P(2)(1) against a high dose (80 Gy) of X-ray radiation.…”
mentioning
confidence: 99%
“…Decreased activity of superoxide dismutase (SOD, a radical scavenger) and generation of malondialdehyde (MDA, a lipid peroxidation end product) in organisms are biomarkers of radiation-induced damage [53][54][55] . Thus, the levels of SOD and MDA in the embryos were measured ( Fig.…”
mentioning
confidence: 99%